-5x+7-3x=-4x-5-2x

Simple and best practice solution for -5x+7-3x=-4x-5-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+7-3x=-4x-5-2x equation:


Simplifying
-5x + 7 + -3x = -4x + -5 + -2x

Reorder the terms:
7 + -5x + -3x = -4x + -5 + -2x

Combine like terms: -5x + -3x = -8x
7 + -8x = -4x + -5 + -2x

Reorder the terms:
7 + -8x = -5 + -4x + -2x

Combine like terms: -4x + -2x = -6x
7 + -8x = -5 + -6x

Solving
7 + -8x = -5 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
7 + -8x + 6x = -5 + -6x + 6x

Combine like terms: -8x + 6x = -2x
7 + -2x = -5 + -6x + 6x

Combine like terms: -6x + 6x = 0
7 + -2x = -5 + 0
7 + -2x = -5

Add '-7' to each side of the equation.
7 + -7 + -2x = -5 + -7

Combine like terms: 7 + -7 = 0
0 + -2x = -5 + -7
-2x = -5 + -7

Combine like terms: -5 + -7 = -12
-2x = -12

Divide each side by '-2'.
x = 6

Simplifying
x = 6

See similar equations:

| 10y+19x= | | -4*(20-(1/3*x)) | | 0=0.2(5x+6)+1.2 | | 10y+19x+16x+4z= | | -4*(20-(1/3*x | | (X/3)-(x/4)=20 | | h(x)=2x-6 | | 2(x-2)3=3(2x+6) | | X/3-x/4=20 | | 9/8*c-2c=13 | | -(-x+4)+2x-3+x^2=x^2-4x+14 | | 147=4.9x-38 | | y=x+420 | | 6*(x-5)=6*x-6*5 | | (10y-8)-(40x+20y-7)= | | t(4t-9)=0 | | 96=8.5x | | .85x=96 | | 85/100=96/x | | 7/4-3/5 | | 3x+39=3x-71 | | Y=a/1-h | | 2x-4)*(5/7) | | 3x+4x=100+4x | | -4/3=2/32 | | f(x)=15x^2-40x | | 2(x-9)+6=8x | | 2x(10+x)=1(x+42) | | 188.49=1/2*3.14*r^2*5 | | r=((3*188.49)/(3.14*5))^1/2 | | 5x=-3x+38 | | 5x=-3+38x |

Equations solver categories